Students’ Perception On The Use Of Tiktok As An Effective Learning Media In Improving Students’ Vocabulary - M. Abhi Rama; Zohri Hamdani; Candraning Prihatini (Departement of Mathematics Education, 2023)
By using the aforementioned characters, it is hoped that students'' vocabulary mastery will go beyond simply knowing the definitions of the words. This is especially true for words and phrases that are commonly used or found on social media, such as Tiktok. Students'' language proficiency increases with the size of their vocabulary. They can mold their English and consider it one of their school topics by developing their vocabulary. The authors were motivated to conduct this study to learn more about the impact of social media platforms like Tiktok on vocabulary development in pupils based on the information and issues mentioned above. Pre-experimental research using a quantitative method was the research design used in this study. The researchers chose this approach because it provided a quantitative study design that was used to share questionnaires. The results of the survey show that students have a positive attitude towards using TikTok to learn English vocabulary. Due to the variety of vocabulary levels available, TikTok significantly helps students improve their English vocabulary. In addition, TikTok''s many engaging elements help to effectively improve students' vocabulary. In conclusion, TikTok is a technology tool that has a significant impact in many different areas. The use of TikTok in language learning increases students'' motivation to learn and is successful in acquiring English vocabulary.